Application of Alum Sludge in Phosphate Phosphorus Removal from Contaminated Water - Ojha, B; Sharma, R K; Amatya, I. M. (Journal of the Institute of Engineering, 2019)
This study determines application of alum sludge in phosphate phosphorus (PO43-/P) removal from contaminated water. For the study the alum sludge was collected from Mahankal Water Treatment Plant and dewatered by drying in micro oven under 105°C and crumble to average particle size of 5 mm. 10.7 ppm Synthetic PO43-/P solution was prepared by dissolving Na2HPO4.2H2O. Batch test was conduct to determine the PO43-/P removal efficiency and to develop adsorption isotherm. The phosphorus removal efficiency was tested for 8 g, 16 g, 24 g, 32 g and 40 g alum sludge per L PO43-/P solution for different contact time. The PO43-/P content in the sample solution was determine by L-Ascorbic Acid method using Spectrophotometer (Shimadzu UVmini-12400) in the lab of Pulchowk Campus, Institute of Engineering Tribhuvan University. The PO43-/P removal efficiency was found to be 95.5% for 8 g/L dosing and 98.4% % for 40 g/L. The contact time decreases with increase in dosing 50 min for 8 g/L and 5 min for 40 g/L dosing. The adsorption process best fit Freundlich isotherm with higher correlation coefficient (R2 = 0.87) and Freundlich intensity parameter (1/n) less than unit (1/n = 0.76) upto 50min contact time and beyond 50min contact time intensity parameter (1/n) greater than unit. The adsorption capacity determine from isotherm indicate increase in adsorption capacity with increase in dosing. The adsorption capacity increases from 1.39 to 28.07 mg/g when contract time varies from 1 to 120min.